2020
DOI: 10.1177/1535370220911604
|View full text |Cite
|
Sign up to set email alerts
|

Copper promotion of myocardial regeneration

Abstract: Myocardial regeneration is the key to the functional recovery of ischemic heart. Angiogenesis plays a pivotal role in myocardial regeneration by resetting a rejuvenation microenvironment under ischemic conditions. Hypoxia-inducible factor 1 (HIF-1) is the predominant transcription factor in the regulation of angiogenesis. In prolonged myocardial infarction, HIF-1α, the critical subunit of HIF-1, is accumulated in the infarcted myocardium, but fails to activate angiogenesis, suggesting a missing of a critical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 105 publications
(157 reference statements)
0
14
0
Order By: Relevance
“…According to Klevay et al ( 42 ), copper was an antioxidant, a constituent of monoamine oxidase and SOD, which benefited the blood vessel wall’s fiber’s by maintaining their toughness and suppleness. Copper had been shown to promote cardiac regeneration by reactivating hypoxia inducible factor 1-regulated angiogenesis, constituting another therapeutic strategy for ischemic heart disease ( 43 ). Molecular biology studies had shown that copper functioned in different organelles as a cofactor for proteins and enzymes required for cytoplasmic maturation and enzyme production ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Klevay et al ( 42 ), copper was an antioxidant, a constituent of monoamine oxidase and SOD, which benefited the blood vessel wall’s fiber’s by maintaining their toughness and suppleness. Copper had been shown to promote cardiac regeneration by reactivating hypoxia inducible factor 1-regulated angiogenesis, constituting another therapeutic strategy for ischemic heart disease ( 43 ). Molecular biology studies had shown that copper functioned in different organelles as a cofactor for proteins and enzymes required for cytoplasmic maturation and enzyme production ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of previous discussion, copper primarily can connect two trophic factors; it promotes angiogenesis stimulating VEGF production and wound healing [129], while the underlying mechanism involves the transcriptional activity of HIF-1α that modulates VEGF expression [156,157].…”
Section: Discussionmentioning
confidence: 99%
“…The immunofluorescence of eNOS and CD31 on groups of R‐GHK‐Cu (5%,10%) was significantly increased compared to that of the control groups, indicating an enhancement of angiogenesis in R‐GHK‐Cu (5%, 10%) treated skin tissues. It was reported copper ions can not only upregulate the expression of angiogenic factors for VEGF and angiogenin, [ 30,31 ] but also enhance tissue regeneration via the regulation of endothelial cell survival, proliferation, and migration. [ 7,32 ] Here in our strategy copper ion was chelated and functioned its role by binding with the peptides GHK, which is highly similar to its existence form in biological system.…”
Section: Discussionmentioning
confidence: 99%